Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng (Zootaxa, 2017)
The genus Doryscus Jacoby, 1887 is revised. Twelve new species are described: D. indochinensis sp. nov. from China (Yunnan), India, Laos, Thailand, Vietnam; D. krausi sp. nov. from Laos and Thailand; D. kubani sp. nov., from China (Yunnan); D. geiseri sp. nov. from Singapore and Thailand; D. nepalensis sp. nov. from Bhutan, north India, and Nepal; D. luzonensis sp. nov., and D. mindanaoensis sp. nov. from Philippines; D. barclayi sp. nov., D. boreri sp. nov., D. javanensis sp. nov., and D. sumatrensis sp. nov. from Indonesia; D. wangi sp. nov. from East Malaysia (Sabah). Doryscus chujoi Takizawa, 1978 and D. varians (Gressitt & Kimoto, 1963) are removed from synonymy with D. testaceus Jacoby, 1887. Doryscus nigricollis Jiang, 1992 and D. marginicollis Jiang, 1992 are regarded as junior synonyms of D. varians (Gressitt & Kimoto, 1963). A lectotype is designated for Doryscus testaceus Jacoby, 1887.